1976
DOI: 10.1677/joe.0.0680181
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cortisol, Cortisone, 11-Deoxycortisol and Corticosterone in Foetal Sheep Plasma During the Perinatal Period

Abstract: A method is described for the resolution and individual quantitation of cortisol, cortisone, 11-deoxycortisol and corticosterone in foetal sheep plasma. The steroids were extracted by solvent partition and separated by LH-20 Sephadex column chromatography. Radioimmunoassay was used for the measurement of 11-deoxycortisol and cortisone and competitive protein-binding for corticosterone and cortisol. The relative levels of these steroids in the plasma of chronically catheterized sheep foetuses from 12 days befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Smith (20) reported that the concentration of 11-dehydrocorticosterone ex ceeded that of corticosterone in the fetal rat over the last 5 days of gestation, but as these values were obtained by extracting whole fe tuses, little can be concluded as to the levels in blood. Surprisingly, Thomas et al (23) could not detect E in the plasma of fetal sheep despite the presence of substantial amounts of F. Nothing has been reported on the activity of 110-hydroxysteroid dehydrogenase in tissues of this species. In the fetal rabbit we have found that the F/E ratio in blood remains close to unity apart from at day 25, when it increases sharply; this is primarily due to a sixfold in crease in the concentration of F. The increase coincides, perhaps fortuitously, with an in crease in the concentration of E and F maternal plasma.…”
Section: Discussionmentioning
confidence: 90%
“…Smith (20) reported that the concentration of 11-dehydrocorticosterone ex ceeded that of corticosterone in the fetal rat over the last 5 days of gestation, but as these values were obtained by extracting whole fe tuses, little can be concluded as to the levels in blood. Surprisingly, Thomas et al (23) could not detect E in the plasma of fetal sheep despite the presence of substantial amounts of F. Nothing has been reported on the activity of 110-hydroxysteroid dehydrogenase in tissues of this species. In the fetal rabbit we have found that the F/E ratio in blood remains close to unity apart from at day 25, when it increases sharply; this is primarily due to a sixfold in crease in the concentration of F. The increase coincides, perhaps fortuitously, with an in crease in the concentration of E and F maternal plasma.…”
Section: Discussionmentioning
confidence: 90%
“…They then increase progressively up to G140 to enhance dramatically just before birth when they can reach 100 ng/mL (see fig 1 In the newborn lamb, they decrease within a few days to levels similar to those found in the adult (around 4 ng/mL) (Alexander et al, 1968;Brown et al, 1978;Magyar et al, 1980). From G100 on, fetal ovine plasma contains aldosterone, corticosterone, cortisol, 11-deoxycortisol and 11-deoxycorticosterone (Wintour et al, 1975;Thomas et al, 1976;Brown et al, 1978).…”
Section: Fetal Plasma Levels Of Corticosteroidsmentioning
confidence: 75%
“…It is only from G120 onwards that the fetus starts producing cortisol (Wintour et al, 1980 (Cathiard et al, 1985). The cortisol/corticosterone ratio varies throughout gestation (Thomas et al, 1976;Brown et al, 1978 (Thomas et al, 1976;Brown et al, 1978;Wintour et al, 1995).…”
Section: Fetal Plasma Levels Of Corticosteroidsmentioning
confidence: 99%
“…However, as the main hormones released by the fetus and newborn adrenals were reported to change during development in several species in cluding rat [25], sheep [46] and rabbit [19], one could speculate that these drastic changes in adrenal activity are related to the evolu tion of the different molecular forms of ACTH during the perinatal period. Such a hypothesis needs further investigations.…”
Section: Discussionmentioning
confidence: 99%